2018
DOI: 10.15557/jou.2018.0015
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound image of malignant bone tumors in children. An analysis of nine patients diagnosed in 2011–2016

Abstract: Introduction: The diagnostic process of bone tumors, including malignant ones, is based on conventional radiological methods, such as radiography and computed tomography, and with precise assessment of local advancement in magnetic resonance imaging. Ultrasonography is not included in the diagnostic algorithms as a tool suitable to detect this type of pathology. More and more frequent usage of musculoskeletal ultrasound in children as the first imaging method or, in some cases, as the only diagnosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…28 Inter-estingly, a 2018 article explored the use of USE beyond soft tissue tumors by reporting a case series of bone tumors in children. 31 The authors reported that most malignant bone tumors were very stiff. 31…”
Section: Nervesmentioning
confidence: 99%
“…28 Inter-estingly, a 2018 article explored the use of USE beyond soft tissue tumors by reporting a case series of bone tumors in children. 31 The authors reported that most malignant bone tumors were very stiff. 31…”
Section: Nervesmentioning
confidence: 99%
“…Similar findings in inflammatory abnormalities were observed, including osteomyelitis and fractures. 31 Using colour Doppler imaging, ultrasound examines flow direction and velocity within a specified area via intermittent samples of ultrasound waves. 32 This feature allowed for the visualisation of malignant tissue communicating with bone and assessment of neoplasm vasculature without the need to administer contrast media.…”
Section: Recommendations For Practicementioning
confidence: 99%
“…32 This feature allowed for the visualisation of malignant tissue communicating with bone and assessment of neoplasm vasculature without the need to administer contrast media. 31 Additionally, just like MRI, ultrasound was able to categorise tumours morphologically by identifying any cystic components, areas of necrosis or haemorrhagic cysts. 31 An imaging protocol that distinguishes between these differential diagnoses must be developed to reduce the need for radiographic imaging.…”
Section: Recommendations For Practicementioning
confidence: 99%
See 1 more Smart Citation
“…It is important that clinicians and radiologists are aware of the range of articular abnormalities that can masquerade as arthritis. This is particularly important when faced with a patient presenting with a monoarticular disease (24,25) . There is also a large group of traumatic lesions, presenting with the same features as JIA like pain, swelling, limited movement.…”
Section: Jia Mimickers and Other Possible Findings In Msusmentioning
confidence: 99%